Dendrimers: A Themed Issue in Honor of Professor Donald A. Tomalia on the Occasion of His 85th Birthday, Recognizing His Outstanding Achievements in Advancing the Field of Dendrimers - Anne-Marie Caminade (Pharmaceutics)
As the main pioneer in the field of dendrimers, a term that he coined in 1985 in reference to their tree-like structure, Prof. Donald A. Tomalia has inspired several generations of researchers worldwide [...]